Impact of Intraoperative Dexamethasone After Scheduled Cesarean Delivery: A Retrospective Study. Issue 4 (December 2020) - Nanji, J.; Guo, N.; Riley, E.; Carvalho, B.
Abstract : ( Int J Obstet Anesth . 2020;41:39–46) In current anesthesia practice, a common preventative medication for postoperative nausea and/or vomiting (PONV) is dexamethasone. However, its efficacy when administered as a single intraoperative dose for procedures performed under spinal anesthesia is unclear. Analgesic effects of dexamethasone administered in the perioperative period have also been described in the literature. The investigators of this impact study aimed to determine the postoperative benefits from the administration of a single dose of intravenous (IV) dexamethasone during cesarean delivery (CD) performed under spinal or combined spinal epidural (CSE) anesthesia.